EFEKTIVITAS YOGA TERHADAP NYERI DISMENORE PADA REMAJA - Melda Friska Manurung; Sri ' Utami; Siti Rahmalia HD ' Rahmalia HD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Dysmenorrhea is increasing and excessive pain during menstruation. There is some pain management to overcome the pain of dysmenorrhea, one of which is with yoga. This study aims to determine the effectiveness of yoga to decrease the intensity of dysmenorrhea pain. The design of this research study